The Chemistry Profile of Essential Oil of the Roots, Stems, and Leaves of The Plant Litsea firma (Blume) Hook F. - Rafiunisa, Rafiunisa; Muharini, Rini; Erlina, Erlina (Chimica et Natura Acta, 2026)
Indonesia, as an agrarian country rich in natural resources, holds enormous potential in the essential oil industry. There are approximately 150–200 species of essential oil-producing plants worldwide, 40 of which are found in Indonesia, including those from the Lauraceae family. The genus Litsea within the Lauraceae family is known for producing essential oils, with Litsea cubeba being the most popular. However, high demand for Litsea’s essential oils encourages the exploration of essential oils from other Litsea species, such as Litsea firma. This study used gas chromatography-mass spectrometry to look at the chemical profile of essential oils from the roots, stems, and leaves of L. firma grown in West Kalimantan. The chemical profile data is then compared with data from other studies. The analysis results indicated that the composition of essential oils from roots is similar to the stems but differs from the leaf. The stem and root essential oils primarily consist of 4,4-diethyl-spiro[2,3]hexan-5-on, whereas the leaf essential oils mostly contain 1-cyclohexyl-ethanone. This difference in chemical constituents suggests that different parts of L. firma may have different ecological roles or therapeutic benefits. Further research could explore the implications of these findings for the plant's potential use in traditional medicine or natural product development. Therefore, we should continue exploring L. firma's essential oil to maximize its potential.